Long-Lasting Effects of the Pandemic on Older Adults' Food Insecurity: The Urgent Need for Enhanced SNAP Benefits. (17th December 2021) - Popham, Lauren; Tavares, Jane; Cohen, Marc
Abstract: Despite the start of COVID-19 pandemic recovery in the U.S., food insecurity remains at elevated levels with 10% of American adults reporting food insecurity nearly three times higher than pre-pandemic (Census Bureau's Household Pulse Survey, June 2021). To gain insight into the long-term impacts of the pandemic on older adults, we examined food insecurity patterns during the last economic recession and the role that the Supplemental Nutrition Assistance Program (SNAP) played in mitigating food insecurity and skipped meals. We analyzed data on adults age 60+ from the Health and Retirement Study, looking at the Great Recession (2008) as a predictor of what to expect in the next decade of pandemic recovery. A key finding was that food insecurity more than doubled among older adults during the Great Recession and remained elevated even 10 years later. Regression analyses showed that SNAP use among older adults weakened the relationship between poverty and food insecurity, but didn't eliminate it—17% of older adults still reported food insecurity two years after enrolling in SNAP. The data indicates that a growing share of older SNAP users' benefits have not kept up with rising food costs. In fact, 85% of beneficiaries had monthly benefit amounts below the USDA 'Thrifty Plan" budget. Congress recently passed the American Rescue Plan which increases SNAP benefits temporarily, yet these enhancements are about to run out. This study underscores the need for permanent SNAP enhancements to help prevent long-lasting hunger facing millions of older Americans.